Are service quality and travel satisfaction two different variables? - Dong, Hao; Hashim, Haslinda; Kamarulzaman, Nitty Hirawaty (Human Resource Management Academic Research Society, 2024)
Many governments actively encourage citizens to switch travel mode from private cars to public transport to alleviate urban traffic problems. Improving the service quality and travel satisfaction of public transport is widely recognized as a practical approach to reach this target. However, scholars have debated whether service quality and travel satisfaction are separate constructs. Some scholars consider them to be two different concepts, while others consider them to be the same concept. This literature needs to be reviewed and synthesized. Successfully differentiating between service quality and travel satisfaction will effectively inform marketing strategies. Therefore, this study employs a literature review approach to the review of current literature. The results indicate that (1) there is indeed measurement ambiguity between service quality and travel satisfaction in transport behavior research. (2) The measurement of travel satisfaction needs to be based on subjective well-being, which belongs to affective factors, while the assessment of service quality relies on cognitive dimensions. Finally, the results are discussed and summarized, and provide suggestions for future research. This paper can provide research references for travel mode choice behavior and provide research value for the application of service quality and travel satisfaction.